Statistical techniques in human population genetics - Hellenthal, Garrett (Henry Stewart Talks, 2016)
Describe the biological & demographic processes that contribute to genetic diversity, Describe statistical techniques that use observed DNA patterns to infer these past processes, Illustrate the types of data used for inferring human history, Highlight some key findings about human history derived through the use of these techniques